Citrullinated histone H3, a biomarker of neutrophil extracellular trap formation, predicts the risk of venous thromboembolism in cancer patients. (7th February 2018) - Mauracher, L.‐M.; Posch, F.; Martinod, K.; Grilz, E.; Däullary, T.; Hell, L.; Brostjan, C.; Zielinski, C.; Ay, C.; Wagner, D. D.; Pabinger, I.; Thaler, J.
Abstract : Essentials Neutrophil extracellular traps (NETs) might play a role in cancer‐related coagulopathy. We determined NET biomarkers and followed cancer patients for venous thromboembolism (VTE). We found a constant association with VTE for citrullinated histone H3. Biomarkers of NET formation could reflect a novel pathomechanism of cancer‐related VTE. Summary: Background: Neutrophil extracellular traps (NETs) are decondensed chromatin fibers that might play a role in the prothrombotic state of cancer patients. Objectives: To investigate whether the levels of citrullinated histone H3 (H3Cit), a biomarker for NET formation, cell‐free DNA (cfDNA) and nucleosomes predict venous thromboembolism (VTE) in cancer patients. Patients/Methods: Nine‐hundred and forty‐six patients with newly diagnosed cancer or progression after remission were enrolled in this prospective observational cohort study. H3Cit, cfDNA and nucleosome levels were determined at study inclusion, and patients were followed for 2 years. VTE occurred in 89 patients; the cumulative 3‐month, 6‐month, 12‐month and 24‐month incidence rates of VTE were 3.7%, 6.0%, 8.1%, and 10.0%, respectively. Results: Patients with elevated H3Cit levels (> 75th percentile of its distribution, n = 236) experienced a higher cumulative incidence of VTE (2‐year risk of 14.5%) than patients with levels below this cut‐off (2‐year risk of 8.5%, n = 710). In a competing‐risk regression analysis, a 100 ng mL −1 increase in H3Cit level was associated with a 13% relative increase in VTE risk (subdistribution hazard ratio [SHR] 1.13, 95% confidence interval [CI] 1.04–1.22). This association remained after adjustment for high VTE risk and very high VTE risk tumor sites, D‐dimer level, and soluble P‐selectin level (SHR 1.13, 95% CI 1.04–1.22). The association of elevated nucleosome and cfDNA levels with VTE risk was time‐dependent, with associations with a higher risk of VTE only during the first 3–6 months. Conclusion: These data suggest that biomarkers of NET formation are associated with the occurrence of VTE in cancer patients, indicating a role of NETs in the pathogenesis of cancer‐associated thrombosis.